Pathways to Self-Stigma in Parents of Children with a Mental Health Disorder. - Eaton, Kim; Stritzke, Werner G. K.; Corrigan, Patrick W.; Ohan, Jeneva L. (Journal of Child & Family Studies, 2020)
Objectives: Self-stigma in parents of children with a mental health disorder is a painful experience, yet the process by which it is formed is poorly understood. A model of this process would improve our understanding and inform intervention development. The two existing models of self-stigma have not been tested with parents of children with a mental health disorder specifically, and are inconsistent with qualitative research findings suggesting an alternative explanation. Thus, this study aimed to test a model of parents' self-stigma drawn from qualitative research, in which parents' awareness of stigma predicts parents' self-doubt about their parenting, self-doubt predicts self-stigma, which in turn predicts affective distress. Methods: Parents of children with a mental health disorder (n = 424) completed measures representing each of these model components. Results: Using structural equation modelling and after controlling for child symptoms and demographics, significant direct pathways were found from awareness of stigma to self-doubt, self-doubt to self-stigma, and self-stigma to affective distress. Conclusions: These findings suggest that self-doubt is an important step in internalising stigma as self-stigma. Furthermore, self-stigma is related to serious consequences for parents' psychological wellbeing and hence, the parent-child relationship. Findings are discussed in terms of their implications for theory and self-stigma interventions.